Gait Variability in Spinocerebellar Ataxia Assessed Using Wearable Inertial Sensors - Shah, Vrutangkumar V.; Rodriguez‐Labrada, Roberto; Horak, Fay B.; McNames, James; Casey, Hannah; Hansson Floyd, Kyra; El‐Gohary, Mahmoud; Schmahmann, Jeremy D.; Rosenthal, Liana S.; Perlman, Susan; Velázquez‐Pérez, Luis; Gomez, Christopher M. (Movement disorders, 2021)
Background Quantitative assessment of severity of ataxia‐specific gait impairments from wearable technology could provide sensitive performance outcome measures with high face validity to power clinical trials. Objectives The aim of this study was to identify a set of gait measures from body‐worn inertial sensors that best discriminate between people with prodromal or manifest spinocerebellar ataxia (SCA) and age‐matched, healthy control subjects (HC) and determine how these measures relate to disease severity. Methods One hundred and sixty‐three people with SCA (subtypes 1, 2, 3, and 6), 42 people with prodromal SCA, and 96 HC wore 6 inertial sensors while performing a natural pace, 2‐minute walk. Areas under the receiver operating characteristic curves (AUC) were compared for 25 gait measures, including standard deviations as variability, to discriminate between ataxic and normal gait. Pearson's correlation coefficient assessed the relationships between the gait measures and severity of ataxia. Results Increased gait variability was the most discriminative gait feature of SCA; toe‐out angle variability (AUC = 0.936; sensitivity = 0.871; specificity = 0.896) and double‐support time variability (AUC = 0.932; sensitivity = 0.834; specificity = 0.865) were the most sensitive and specific measures. These variability measures were also significantly correlated with the scale for the assessment and rating of ataxia (SARA) and disease duration. The same gait measures discriminated gait of people with prodromal SCA from the gait of HC (AUC = 0.610, and 0.670, respectively). Conclusions Wearable inertial sensors provide sensitive and specific measures of excessive gait variability in both manifest and prodromal SCAs that are reliable and related to the severity of the disease, suggesting they may be useful as clinical trial performance outcome measures. © 2021 International Parkinson and Movement Disorder Society